Alternating carnivore and Neanderthal activities at Escoural Cave: insights from the taphonomic and machine learning analysis of leporid remains - Cobo-Sánchez, Lucía; Rufà, Anna; Cascalheira, João (Frontiers in Environmental Archaeology, 2024)
Exploring the varied subsistence strategies and cave occupation patterns of Neanderthals is key to understanding their complex behaviors and ecological adaptations. Small game consumption, in particular, is considered a relevant indicator of their behavioral complexity. Rabbit assemblages from Pleistocene cave sites provide valuable insights into Neanderthal interactions with small prey and potential competition with carnivores. Here, we present the first detailed taphonomic analysis of faunal remains from Escoural Cave (Portugal), where a European rabbit (Oryctolagus cuniculus) assemblage was found alongside Middle Paleolithic stone tools and some macromammal remains. This study combines traditional zooarchaeological and taphonomic analysis of the rabbit remains with multivariate statistics and machine learning methods to establish the origin of the accumulation, and the implications for Neanderthal subsistence and cave use. Results from the taphonomic analysis show no evidence of human consumption but abundant evidence of small terrestrial carnivore activity, primarily from lynxes. This could indicate a sequential occurrence of Neanderthal and carnivore activities in the cave, with Neanderthal activities likely related to something other than rabbit consumption. Our study contributes to characterizing Iberian carnivore fossil accumulations and differentiating between faunal assemblages accumulated by carnivores and those by hominins. Additionally, we show that the use of machine learning analysis provides a robust and objective method for identifying and classifying taphonomic signatures, enhancing the accuracy and reliability of our interpretations. Future work will focus on analyzing additional faunal collections from both past and new excavations at Escoural, to test whether carnivores and Neanderthals focused on different prey types and how they shared the cave space.